Desain Sistem Monitoring Sistem Photovoltaic Berbasis Internet of Things (IoT) - Winasis; Azis Wisnu Widhi Nugraha; Imron Rosyadi; Fajar Surya Tri Nugroho (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2016)
Photovoltaic (PV) system is an alternative solution to provide electricity at rural area. A common implementation problem at rural area is the PV power plant cannot be monitored continuously. This research proposes wireless node for PV power plant monitoring based on Internet of Things (IoT). Wireless node is aimed for monitoring electrical parameter from the PV and environmental parameter (temperature and solar radiation). Measured parameters are sent to the cloud database to be accessible via the internet. The device consist of a sensor module, signal processing module and wireless transceiver module. Wireless transceiver module is an ESP8266 for connection to the IoT gateway and to the internet. Unidirectional ACS758 is used for current sensing, which give a reading error of 0.091 Ampere. For voltage sensing, a voltage divider is used. It has a reading error of 0.063 Volt. DHT22 is used for temperature sensing. Its reading error is 0.0097 °C. The radiation sensor has a reading error of 0.3 W/m2. Proposed design has been tested at Laboratorium of Energy Convertion, Electrical Engineering Department, UNSOED, on 300Wp PV system. This device provides reliable monitoring data transmission with average and deviation in delivery time consecutively 57 seconds and 2 seconds.